A false-positive result at non-invasive prenatal testing due to maternal 17p12 microduplication - Chih-Ping Chen; Shin-Wen Chen; Peih-Shan Wu; Fang-Tzu Wu; Wayseen Wang (Elsevier, 2022)
Objective: We present a false-positive result at non-invasive prenatal testing (NIPT) due to maternal 17p12 microduplication. Case report: A 37-year-old, gravida 2, para 1, woman underwent amniocentesis at 19 weeks of gestation because of advanced maternal age. Amniocentesis revealed a karyotype of 46,XY. Simultaneous array comparative genomic hybridization (aCGH) revealed the result of a 1.3-Mb duplication of 17p12 or arr [GRCh37] 17p12 (14,111,772-15,442,066) × 3 encompassing four Online Mendelian Inheritance in Man (OMIM) genes of COX10, HS3ST3B1, PMP22 and TEKT3. The mother did not have any neurologic problems. The parents were phenotypically normal. aCGH analysis of maternal blood revealed that the mother carried the same 17p12 microduplication. Two years ago, NIPT analysis during her first pregnancy revealed abnormality of chromosome 17 with 17p11.2p12 duplication. However, subsequent aCGH analysis at amniocentesis revealed no genomic imbalance in the fetus, and no further examination of the parental bloods was made. During this pregnancy, prenatal ultrasound was unremarkable, and the parents decided to continue the pregnancy. Conclusion: A false-positive result at NIPT should raise a suspicion of maternal genomic imbalance.